R Factor Proteins Synthesized in Escherichia coli Minicells: Incorporation Studies with Different R Factors and Detection of Deoxyribonucleic Acid-Binding Proteins - Levy, Stuart B. (1974)
Analysis of the protein synthesized by Escherichia coli minicells containing R factors demonstrated a variety of low- and high-molecular-weight polypeptides in sodium dodecyl sulfate (SDS)-polyacrylamide gels. Only half of this protein was released into a soluble fraction on lysis of these minicells. The other half remained associated with the minicell envelope. The efficiency of precursor incorporation into protein and the kinds of proteins synthesized changed with the age of the minicells at the time of harvest. About 1 to 2% of the soluble R factor-coded protein bound to calf thymus, E. coli, or R factor DNA-cellulose. Although most of these proteins were excluded from Sephadex G-100 columns, they migrated chiefly as low-molecular-weight-polypeptides (13,000 to 15,000) in SDS-polyacrylamide gels. Additional DNA-binding proteins that appeared to be higher-molecular-weight peptides were noted in extracts from younger minicells. At least one protein, identified as an SDS band, appeared to bind selectively to R factor DNA-cellulose. Minicells with R factors also contained DNA-binding proteins of cell origin, including the core RNA polymerase. No such binding proteins were found in R(−) minicells. These studies suggest that: (i) R factors code for proteins that may be involved in their own DNA metabolism; (ii) R factor DNA-binding proteins may be associated with larger host cell DNA-binding proteins or subunits of larger R factor proteins; and (iii) the age of the minicell influences the extent of protein synthesis and the kinds of proteins synthesized by R factors in minicells.